Disposal of oily cuttings by downhole fracturing injections: slurry product specifications issues - Junin, Radzuan (Faculty of Chemical & Natural Resources Engineering, 1994)
The technique of using on-site injection of oil contaminated drill cuttings is attracting considerable attention as a cost effective means of complying with environmental legistation concerning discharge of drilling wastes. The slurrification and injection of oil based cuttings into a casing annulus, a process developed in 1989 by a majjor oil and gas producer/operator, has proven to be a significant step toward reduction of such environmental waste. This paper discusses the development of the cuttings reinjection, slurrification, slurry properties and benefits of quality slurry, and behaviour of soild laden slurries in a fracture in conjuction with downhole disposal operations.